Symptoms and Causes: Gender Effects and Institutional Failures - Nigar Hashimzade; Natalia Vershinina (ifo DICE Report, 2017)
The existence and causes of gender gaps in pay and in occupational choice have been increasingly at the centre of research in economics, sociology, psychology, managerial science, and other fields. The research findings across countries and over time generally suggest that gaps exist and are significant, indicating that gender inequality remains persistent in many areas, even in the developed Western democracies. Forcefully closing the gaps directly, however, may not be sufficient in the long run. Trying to fix the symptoms without addressing the causes is likely to create other distortions and lead to further welfare losses over time. One hotly debated issue is that of the gender effect on business performance. Women are in a striking minority when it comes to managerial roles and entrepreneurship. According to Terjesen, Aguilera and Lorenz (2015), in 2013 the average proportion of women on the corporate board of directors across 67 countries was only 10.3 per cent, although empirical evidence suggests that higher presence of women on corporate boards is often positively correlated with various measurements of high performance. For example, according to the Fawcett Society (2013), 'companies with more women on their boards were found to outperform their rivals with a 42 per cent higher return in sales, 66 per cent higher return on invested capital and 53 per cent higher return on equity'. Do women make better leaders, better managers, better 'bosses', and, if yes, why don't we see more women than men in these roles? A broad answer to this question is institutional failure, including both formal and informal institutions. Many countries have outlawed gender discrimination and have legislated measures towards eliminating gender gaps. However, even in these countries societal norms and perceptions often lag behind. Failure to realize gains from equal opportunities ultimately leads to a misallocation of human and physical resources and thus to social welfare loss. The answer to the question whether women make better leaders is trickier. A study by Martinsen and Glasø (2013) has concluded that female managers outperform their male counterparts in four out of five categories of leadership characteristics. Among about 3,000 managers, women were better at initiative and clear communication, openness and ability to innovate, sociability and supportiveness, and methodical management and goal-setting, while men were better at dealing with work-related stress and in maintaining higher levels of emotional stability. In this regard, the question Gazanchyan, Hashimzade, Rodionova, and Vershinina (2017) attempted to answer is slightly different. If there is a positive effect of female leadership on business performance, could it be because women face higher hurdles than men, and those who succeeded in making it to the top are better than men in similar roles? The approach to this question was to construct a theoretical model linking occupational choice in the presence of gender bias to business performance and to subject the assumptions and predictions of themodel to an empirical test. While the firm-level data set used in this study contained important details of firm characteristics contributing to business performance as well as the information on the gender of the firm owner and senior manager, it provided no information on the personality and characteristics of the owners and managers. Thus, the aim of the research was to compare the performance of firms owned and/or managed by women and those owned and/or managed by men, with all other observable characteristics being similar, or matched: if there is a gap, it can then be attributed to the gender effect. A potential hurdle explored in this work was access to finance in the credit markets for reasons discussed below.
Keywords: J16; J18; J24; 330; Humankapital; Lohnstruktur; Erwerbsverlauf; Führungskräfteauswahl; Wettbewerb; Geschlechterdiskriminierung; Weibliche Führungskräfte; Arbeitsangebot